The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1039/d1ra02291a
|View full text |Cite
|
Sign up to set email alerts
|

A facile preparation of superhydrophobic L-CNC-coated meshes for oil–water separation

Abstract: A superhydrophobic stainless steel mesh (called “mesh” in short) is an ideal device to solve oil pollution accidents by oil–water separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The WCA and UOWCA of SSM, CA coatings without MTCS deposited (C‐5), and CA coatings with MTCS deposited but different in electrostatic spraying times (C‐5‐M to C‐60‐M) are shown in Figure 4B,C. The contact angles of all CA coating samples are almost always above 154°, which is better than those reported in several papers that have been reported 10,27 . This confirms the superhydrophobic properties of the CA coating under air and oil for electrostatic spraying combined with vapor deposition of MTCS.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…The WCA and UOWCA of SSM, CA coatings without MTCS deposited (C‐5), and CA coatings with MTCS deposited but different in electrostatic spraying times (C‐5‐M to C‐60‐M) are shown in Figure 4B,C. The contact angles of all CA coating samples are almost always above 154°, which is better than those reported in several papers that have been reported 10,27 . This confirms the superhydrophobic properties of the CA coating under air and oil for electrostatic spraying combined with vapor deposition of MTCS.…”
Section: Resultssupporting
confidence: 68%
“…Figure 6B illustrates the separation fluxes of C‐60‐M for six different oil compounds and organic‐like solvents, which are ranging from 18644.44 to 23977.77 L·m −2 ·h −1 . The separation efficiencies were all above 99%, which are better than those reported in several papers that have been reported 27–29 . Table 1 is a list of some of the recent research work with reference to this work.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…It has been shown that through the adsorption between the hydroxyl radicals on the surface of the carbon sphere template and the oxygen-containing functional groups and the metal cations, a layer of metal cations can be formed on the carbon sphere template, after which the carbon sphere template is removed by roasting at a certain temperature, and a metal hollow sphere is prepared. [16][17][18][19] However, the method has certain drawbacks in which there is limited adsorption between the oxygen-containing functional groups on the surface of the carbon sphere template and the metal cations, resulting in the formation of very thin shells of hollow microspheres that are prone to collapse. [20][21][22][23][24] Zirconium dioxide is the only metal oxide that is simultaneously acidic, basic, oxidizing and reducing and is a p-type semiconductor material that readily generates oxygen vacancies and interacts with active components as a catalyst carrier.…”
Section: Introductionmentioning
confidence: 99%